CROSS CURRICULAR ENGLISH EDUCATION AND ITS POSSIBLE APPLICATION IN INDONESIAN CURRICULAR SYSTEM - Sukrisno, Alim (Universitas Negeri Semarang, 2012)
This article is about cross curricular English education viewed from its possible application in Indonesian curricular system. Cross curricular education can take place in the form of project work, thematic teaching and so on. In the Indonesian curricular system, cross curricular education manifests itself in bilingual education in which the medium of instruction is English. In junior and senior high schools this programs is better known as RSBI or SBI. Investigation in the field indicates that this program has been prematurely applied since some basic requirements of its application have not been met. Therefore, should this program be continued an investigation must be conducted to see which parts of the program should be modified, replaced, or even removed altogether.